2017
DOI: 10.2147/mder.s113105
|View full text |Cite
|
Sign up to set email alerts
|

Interatrial shunt devices for heart failure with normal ejection fraction: a technology update

Abstract: Heart failure with normal ejection fraction (HeFNEF) accounts for ~50% of heart failure admissions. Its pathophysiology and diagnostic criteria are yet to be defined clearly which may hinder the search for effective treatments. The clinical hallmark of HeFNEF is exertional breathlessness, often due to an abnormal increase in left atrial pressure during exercise. Creation of an interatrial communication to offload the left atrium is a possible therapeutic approach. There are two percutaneously delivered devices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Interatrial shunts 13,14,23,24 Interatrial shunt device Corvia Medical; The Synergy System CircuLite pump is in a left atrial to right axillary artery configuration. Outflow to the right axillary is functionally the same as outflow to the aorta and as such can be used interchangeably here.…”
Section: Devices Manufacturersmentioning
confidence: 99%
See 2 more Smart Citations
“…Interatrial shunts 13,14,23,24 Interatrial shunt device Corvia Medical; The Synergy System CircuLite pump is in a left atrial to right axillary artery configuration. Outflow to the right axillary is functionally the same as outflow to the aorta and as such can be used interchangeably here.…”
Section: Devices Manufacturersmentioning
confidence: 99%
“…This allows for left-to-right shunting and unloading of the left atrium, which has shown to lead to reductions in pulmonary capillary wedge pressure (PCWP) and improved hemodynamics. 13,14 In a 2014 pilot study of patients with HFpEF, IASDs decreased leftsided filling pressure and demonstrated improvements in NYHA functional class, quality of life, and six-minute walk distance. 15 However, such a shunt would not necessarily improve overall cardiac output, as there is no contribution to forward flow and LV dynamics are not directly impacted.…”
Section: Percutaneous Interventions For Rcm and Hcmmentioning
confidence: 99%
See 1 more Smart Citation